Cryopreservation of Equine Semen previously cooled with and without seminal plasma for 12 hours - De Resende, Hélène Lacerda [UNESP]; Oliveira, Jhonnatha Paulo; Ecker, Marcely Karoline Conceição; Guasti, Priscilla Nascimento [UNESP]; Papa, Frederico Ozanam [UNESP]; Jacob, Júlio César Ferraz (My University, 2013)
In the equine species, the use of frozen semen has limiting factors as the need for skilled labor, the high cost of equipment, as well as an appropriate place on the farms to the handling of semen. In order to evaluate the effect of seminal plasma on cooling of equine semen for 12 hours before cryopreservation, this study was conducted with five stallions of Mangalarga Marchador breed, aged between 4 and 8 years old. For this experiment, 15 semen collections were performed, each ejaculate was divided into three groups and each group was divided into two subgroups, using different media extenders (Botu-Semen® and Botu-Turbo®). In Group I (control), the semen was frozen immediately after collection; in Group II, the seminal plasma was maintained during the cooling and in Group III, the seminal plasma was removed before cooling. After thawing, the sperm parameters were analyzed using CASA and membrane integrity was evaluated by the fluorescent probes carboxyfluorescein diacetate and propidium iodide. Statistical analysis was performed by ANOVA and Tukey's test. There was no significant differences (P>0.05) between the semen samples with and without seminal plasma prior to freezing for all sperm parameters evaluated, total motility (50.5 vs 50.6), progressive motility (21.3 vs 24.1) and plasma membrane integrity (26.2 vs 28). The analyzed data showed that the cooling of equine semen for 12 hours before cryopreservation is an effective method that enables a better use of the ejaculate, regardless of maintenance or removal of seminal plasma during the semen storage.
Criopreservação de Sêmen Equino previamente refrigerado com e sem plasma seminal por 12 horas
Keywords: Extender; Fractions of semen; Freezing; Stallion